IMPLEMENTASI MANAJEMEN KESISWAAN DALAM PEMBENTUKAN AKHLAK TERPUJI - M. Iqbal Taufiqurrohman; Hafidz Hafidz (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The purpose of this study is twofold, namely: (1) to describe the types of conjunctions used, and (2) to describe the use of conjunctions in descriptive texts written by students of class IX Tahfizh SMP Muhammadiyah 8 Surakarta. The method used in this research is descriptive qualitative. Qualitative research is a research process to understand human or social phenomena by creating a comprehensive and complex picture that can be presented in words, reporting detailed views obtained from informant sources, and conducted in a natural setting. The data of this research are sentences that use conjunctions in descriptive texts written by students of class IX Tahfizh SMP Muhammadiyah 8 Surakarta. The data source in this research is the description text written by the ninth-grade students of SMP Muhammadiyah 8 Surakarta. The data were analyzed by classifying, analyzing, and discussing the data based on technical theory. The results of this study amounted to 25 data consisting of four types of conjunctions, namely: coordinative conjunctions, correlative conjunctions, subordinative conjunctions, and inter-sentence conjunctions. For the use of conjunctions in the description texts written by students of class IX Tahfizh SMP Muhammadiyah 8 Surakarta, there are 16 inaccurate uses of correlative conjunctions and 5 inaccurate uses of inter-sentence conjunctions. The inaccuracy is caused by students' lack of understanding of the use of conjunctions.